Answer= x²+7x+10
When we want to expand expressions such as this, the FOIL method helps us remember what exactly to do. FOIL stands for
F:First
O:Outer
I:Inner
L:Last
So, given the expression (x+5)(x+2), lets multiply the first two terms.
x*x=x²
now the outer two terms
x*2=2x
now the inner terms
5*x=5x
and the last terms...
5*2=10
When we combine these expressions we get:
x²+7x+10
I think this is what you meant to be answered in your question, if I have been mistaken, just comment and I'll edit my answer....